How much money can buy you happiness, and can happiness be engineered? - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2020)
There may be a lot of misery in the world, opines Chandran Kukathas, but for many, ‘there’s gold in them thar hills’. But can happiness be engineered?